2022
DOI: 10.3164/jcbn.21-153
|View full text |Cite
|
Sign up to set email alerts
|

Increased salt intake is associated with diabetes and characteristic dietary habits: a community-based cross-sectional study in Japan

Abstract: We investigated the association of salt intake with lifestyle-related diseases and also the association of habitually consumed foods with salt intake. A cross-sectional study was conducted using data from a baseline survey of 2,129 residents of Yonezawa city (980 males and 1,149 females), Yamagata prefecture. The residents were divided into three groups based on their estimated daily salt intake: low, medium, and high. In both genders, the prevalence of hypertension and diabetes increased in the order of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, Matti A. Vuori et al has emphasized that high sodium intake is associated with an increased incidence of cardiovascular disease and diabetes ( 29 ). Furthermore, sodium intake adds to the risk of 2 diabetes was widely reported in Asia, such as China, Korea and Japan where pickles and sauces are popular ( 30 32 ). For the first time, our examination of a nationally representative non-institutional members in the United States corroborates previous research indicating a positive correlation between higher sodium intake and an increased risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Matti A. Vuori et al has emphasized that high sodium intake is associated with an increased incidence of cardiovascular disease and diabetes ( 29 ). Furthermore, sodium intake adds to the risk of 2 diabetes was widely reported in Asia, such as China, Korea and Japan where pickles and sauces are popular ( 30 32 ). For the first time, our examination of a nationally representative non-institutional members in the United States corroborates previous research indicating a positive correlation between higher sodium intake and an increased risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research with the UK Biobank found U-shaped relationships between wine intake and reduced diabetes risk [ 35 , 36 ]. Other studies have found a direct association between high salt intake and type 2 diabetes [ 37 , 38 ], but more investigation is needed, given that salt consumption is usually only assessed as a risk factor for hypertension and CVD. However, a link has been reported between high blood pressure and diabetes [ 39 ] and both share biological risk factors and pathophysiological mechanisms [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faced with the challenge of curbing obesity, especially in developed countries, there is a growing focus on intuitive methods of conveying nutritional information (Grummon & Hall, 2020; Mauri et al, 2021). Japanese people generally have good health and long lifespans (Tsugane, 2021), but excessive salt and sugar intake remains a problem among them (Itoh et al, 2022; Wang et al, 2016). In Japan, sweets are traditionally enjoyed by women and children; though, as society's values toward men have changed, adult men have also begun to actively consume foods and drinks containing high amounts of sugar (Holtzman, 2018).…”
Section: Introductionmentioning
confidence: 99%